Socio-spatial segregation in Antofagasta, Northern Chile: the impacts of mining capital - Thodes, Emilio; Batterbury, Simon (AESOP, 2016)
Few countries have been left unaffected by global mining boom. While the direct impacts of large scale mining are felt most strongly in regional areas where mines are directly located, the residual effects of mining are observed in rural and urban landscapes located further afield. In less-developed economies, mining has been one of the major drivers of economic growth and of urban development. Stimulated by the arrival of 'Big Mining', and the influx of capital that comes with it , new sources of development have appeared, particularly through rapid urbanization, the focus of this study (Humphreys & Bebbington 2012). Despite these outcomes, it has been widely acknowledged that mining not only provokes environmental struggles and problems in host regions but it also exacerbates social and economic disparities, transforming urban areas where money and actors circulate. These transformations are not only socio-economic in nature, as they also affect different physical environments and political systems.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south